IMPROVING RESOURCES AND SKILLS FOR MULTI-STAKEHOLDER PARTICIPATION TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Widiyatsih, Tri; Masnunah; Rachmawati, Diana Widhi; Mardiana; Irwansi, Yudi; Utpalasari, Rih Laksmi (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Multi-stakeholder partnerships are one of the important strategies for achieving this, which have an interest in helping to increase resources and expertise, improve coordination and collaboration, build trust and mutual understanding, and increase the accountability of all parties involved in the achievement. Indonesia and Malaysia are two neighboring countries that have many similarities in cultural, economic and social terms, in addition to being strongly committed to joint efforts, where multi-party partnerships between the two countries can play an important role. One of the important roles of multi-stakeholder partnerships is to increase the resources and expertise of the parties involved. This can be done through cooperation, collaboration and synergy.